Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
Step-by-step explanation:
(a+b+c)²=a²+b²+c²+2ab+2bc+2ca
(2x-3y+4z)²=(2x)²+(-3y)²+(4z)²+2(2x)(-3y)+2(-3y)(4z)+2(4z)(2x)
=4x²+9y²+16z²-12xy-24yz+16zx
▬▬▬▬▬▬▬▬▬▬▬▬
We know that,
→ (a + b + c)² = a² + b² + c² + 2ab + 2bc + 2ca
Now Putting 2x = a, -3y = b and 4z = c , we get
→ (2x - 3y + 4z)²
→ (2x)² + (- 3y)² + (4z)² + 2 × 2x × (- 3y) + 2 × (- 3y) × 4z + 2 × 4z × 2x
→ 4x² + 9y² + 16z² - 12xy - 24yz + 16zx
Arranging according to the like terms, we get
→ 4x² - 12xy + 16zx + 9y² - 24yz + 16z²
▬▬▬▬▬▬▬▬▬▬▬▬
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.